Four Weeks of Treatment With Rifaximin Fails to Significantly Alter Microbial Diversity in Rectal Samples of HIV-Infected Immune Non-Responders (ACTG A5286) Which May be Attributed to Rectal Swab Use - Brett B. Williams; Stefan J. Green; Ronald J. Bosch; Ellen S. Chan; Jeffrey M. Jacobson; David M. Margolis; Phillip Engen; Alan L. Landay; Cara C. Wilson (Case Western Reserve University, 2019)
Introduction: HIV-infected individuals have evidence of intestinal microbial translocation which is associated with immune activation and unfavorable clinical outcomes. Rifaximin, a non-absorbable antibiotic which reduces microbial translocation in other disease states, was shown to have a marginal beneficial effect on microbial translocation, T-cell activation, and inflammation in a multisite randomized trial (ACTG A5286; NCT01466595) of HIV-infected persons with poor immunologic recovery receiving ART. Here, we report analysis of the rectal microbiome changes associated with that trial. Methods: HIV-1-infected individuals receiving ART with CD4-T cell count <350cells/mm3 and viral suppression were randomized 2:1 to rifaximin or no therapy for 4 weeks. Rectal swabs were collected at baseline (pre-treatment) and at week 4 of rifaximin therapy. Genomic DNA extracted from rectal swab samples was analyzed using high throughput sequencing and quantitative PCR of bacterial 16S ribosomal RNA (rRNA) genes. Results: Forty-eight HIV-infected participants (31 received rifaximin, 17 no treatment) were included. There was broad variability in the recovery of bacterial rRNA from the specimens at baseline. No major significant (FDR P<0.05) effects of rifaximin treatment on alpha- or beta- diversity or individual taxa were observed between or within the treatment arms, with analyses conducted at taxonomic levels from phylum to genus. Conclusions: Rifaximin did not meaningfully alter the diversity or composition of the rectal microbiome of HIV-infected individuals after 4 weeks of therapy, although rectal swab specimens varied widely in their microbial load.